Tingkat Kepuasan Mahasiswa Terhadap Kinerja Proses Belajar Mengajar (PBM) Dosen - S Paly, Muhammad Basir (Al-Hikmah, 2014)
This study aims to determine the level of studets’s satisfaction of the lecturer PBM performance. Carried out on April-August 2014 at Department of the animal science of Science and Technology Faculty UIN Alauddin Makassar. Factors and indicators of performance refers to the quality manual UIN Alauddin Makassar and Semarang State University (UNNES). A total of 60 samples have been observed. Using survey methods through observation and interviews with a list of questions. Measurement of satisfaction using a scale-linkert with four scales; not-satisfied, less-satisfied, satisfied, and very satisfied. The results showed that the studets’s satisfaction level of the lecturer PBM performance are still dominant among scale "less-satisfied and satisfied". To Increased satisfaction scale be "satisfied and very satisfied" is very possible, through improved performance on some PBM indicators.